P1-N1-P2 Cortical Auditory Evoked Potentials in Chronic Unilateral Acquired Conductive Hearing Loss in Adults - Abeir Osman Dabbous; Noha Ali Hosni; Alzahraa Al-Sayed Owais Emara; Adel Said El-Antably (Journal of International Advanced Otology)
BACKGROUND: Chronic unilateral hearing loss causes imbalanced auditory input to the brain that triggers cortical reorganization. The effect of sensorineural hearing loss on the central auditory system (CAS) has been thoroughly studied, while there is a paucity of research on the effect of conductive hearing loss (CHL). The aim of this study was to assess the P1-N1-P2 cortical auditory evoked response potential (CAEP) in adult individuals with chronic acquired unilateral CHL.